The role of learner engagement with corrective feedback in EFL/ESL classrooms - Liu, Hao; Feng, Mengya (Frontiers in Psychology, 2023)
As corrective feedback (CF) is conducive to students’ second language (L2) development, a considerable number of studies have investigated the effects of different types of CF strategies on EFL/ESL learning achievement. However, the role of learner engagement has been largely neglected in the field of CF research. The present study aims to describe the role of learner engagement with CF in EFL/ESL classrooms by reviewing theoretical and empirical evidence. The findings reveal that learner engagement is indispensable for CF to be effective, and providing strategies for working with CF is essential to guide EFL/ESL learners in their learning process. The implications for teacher CF practice and learner engagement training are also discussed.